2017
DOI: 10.1111/irv.12492
|View full text |Cite
|
Sign up to set email alerts
|

The national burden of influenza‐associated severe acute respiratory illness hospitalization in Zambia, 2011‐2014

Abstract: BackgroundEstimates of influenza‐associated hospitalization are limited in low‐ and middle‐income countries, especially in Africa.ObjectiveTo estimate the national number of influenza‐associated severe acute respiratory illness (SARI) hospitalization in Zambia.MethodsWe conducted active prospective hospital‐based surveillance for SARI at the University Teaching Hospital (UTH) situated in Lusaka Province during 2011‐2014. Upper respiratory tract samples were tested for influenza virus using a reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
77
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(96 citation statements)
references
References 23 publications
(87 reference statements)
12
77
4
Order By: Relevance
“…In two sites, we observed that infants (< 1 year) had the highest influenza-associated SARI hospitalization rates (345 and 495 hospitalizations per 100 000 population) followed by children aged 1–4 years (206 and 338 cases per 100 000 population). Our combined estimates of influenza-associated SARI hospitalizations in children are consistent with findings from African countries ( 19 , 20 ) but higher than those reported for Indonesia and India (82–114 and 118/100 000 children 0–4 years, respectively). ( 21 , 22 )…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In two sites, we observed that infants (< 1 year) had the highest influenza-associated SARI hospitalization rates (345 and 495 hospitalizations per 100 000 population) followed by children aged 1–4 years (206 and 338 cases per 100 000 population). Our combined estimates of influenza-associated SARI hospitalizations in children are consistent with findings from African countries ( 19 , 20 ) but higher than those reported for Indonesia and India (82–114 and 118/100 000 children 0–4 years, respectively). ( 21 , 22 )…”
Section: Discussionsupporting
confidence: 89%
“…( 23 ) In both Zambia and Rwanda influenza-associated hospitalization rates in infants were highest compared to all other age groups (484 and 295/100 000 children < 1 year, respectively), and rates were lowest for the 5–24 years age group (6 and 11/100.000 5–24 years, respectively). ( 19 , 20 ) Compared to the hospitalization rates we estimated for older Cambodian adults, those reported for Zambia and Rwanda were lower (57 and 34/100 000 population > 65 years). ( 19 , 20 )…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…To address this, an analysis exploring the effect of respiratory syncytial virus (RSV) circulation on ARI deaths among children <5 years of age in Bangladesh is underway and similar studies could be conducted in Rwanda. Nonetheless, the estimated influenza‐associated hospitalization rates among children aged <5 years in Rwanda (168 per 100 000 population)3 are similar to those of South Africa (156 per 100 000 population),11 other countries in Africa,8, 9, 12 and global estimates for Africa (174 per 100 000 population) 13. Whereas the circulation patterns of RSV are poorly understood in Rwanda and other African countries, in South Africa, the RSV season precedes and minimally overlaps with the influenza season 24.…”
mentioning
confidence: 79%
“…As such, we do not consider the mortality estimates (6‐11 per 100 000 population) in Bangladesh to be high when compared to other countries; however, we do consider 6‐11 deaths per 100 000 population to be a substantial burden for the country of Bangladesh. Similarly, the estimated influenza‐associated hospitalization rates in Rwanda (34 per 100 000 population) are comparable to those of other African countries situated in equatorial, tropical, and subtropical regions: 21 (95% CI: 19‐23) per 100 000 population in Kenya,8 30 (95% CI: 13‐84) per 100 000 population in Ghana,9 30 (95% CI: 24‐36) per 100 000 population in Madagascar,10 45 (95% CI: 41‐49) per 100 000 population in South Africa,11 and 44 (95% CI: 31‐57) per 100 000 population in Zambia 12. In addition, a global study reported the highest rates of influenza‐associated hospitalization among African children followed by South‐East Asia and the Western Pacific 13.…”
mentioning
confidence: 99%